DUTIES OF A STOMATOLOGY NURSE: A SCIENTIFIC PERSPECTIVE - Akhmedova Makhfuza Boltaevna; Akhmedov Shukhrat Boltaevich (PEDAGOGS, 2024)
Stomatology, or dental medicine, is a specialized field of healthcare that focuses on diagnosing, preventing, and treating conditions related to the oral cavity and its surrounding structures. Within this field, stomatology nurses play a critical role in supporting dental professionals and ensuring high-quality patient care. This article explores the key responsibilities, skills, and contributions of stomatology nurses from a scientific perspective.